Assistance for the Construction of Houses of Worship: One of the Practices of Money Politics in the Context of Criminal Acts in the Perspective of Criminal Law and Islamic Law - Rohmah, Baeti; Nugroho, Raditya Dwi Putranto (Law Research Review Quarterly, 2018)
Money politics seems to be a very difficult thing to eliminate from the realm of elections in Indonesia. In 2018, Bawaslu has received 40 reports of cases of money politics in the simultaneous elections in 2018. One of the modes in the practice of money politics in Indonesia is the provision of assistance in the construction of places of worship which is one form of collective groups in the form. This paper examines how actual money politics is practiced if viewed from the perspective of criminal law and Islamic law. This paper underlines the funding assistance for the construction of places of worship as a practice of money politics in the perspective of criminal law and Islamic law.